IoT-Based Smart Door Lock Design for Multi-Stage Locking in Sterilization Rooms - Muhammad Danny Setiawan; Miftahur Rohman (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2026)
This research presents the design and development of an Internet of Things (IoT)-based Smart Door Lock system implemented in a sterilization room with a step-by-step locking mechanism. The system is designed to improve security and ensure that sterilization procedures are carried out according to standards, where doors can only be accessed sequentially as predetermined. The hardware consists of an ESP32 microcontroller connected to a fingerprint sensor for user authentication and a solenoid door lock as the door actuator. The system is also integrated with an IoT-based server, enabling real-time monitoring of door status through a mobile application. Experimental results show that the system functions properly, allowing doors to open only according to the specified sequence, while access data can be stored and monitored online. Therefore, this Smart Door Lock system provides an effective solution to support both security and operational efficiency in sterilization rooms. Keywords: Smart Door Lock, IoT, ESP32, sterilization room, step-by-step locking.